2006
DOI: 10.1002/anie.200602790
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Macrocyclization of Preorganized Palindromic Oligosquaramides

Abstract: Nature has evolved polymers with highly specific functions. In the last decade, a new generation of natural circular proteins has been found in bacteria, plants, and mammals.[1] These large cycles show exceptional stability and a wide range of [*] Dr.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 16 publications
0
29
0
Order By: Relevance
“…In fact, at sub‐ambient temperatures both the anti – anti and anti – syn ( syn – anti ) isomers are detected by 1 H NMR spectroscopy 21. We also demonstrated that the inclusion of tertiary amino groups as hydrogen bond donors in the vicinity of the squaramido NH groups induces formation of β‐turn analogues in secondary squaramides, allowing the synthesis of oligomeric cyclosquaramides through hydrogen‐bond‐directed macrocyclization 22…”
Section: Introductionmentioning
confidence: 67%
“…In fact, at sub‐ambient temperatures both the anti – anti and anti – syn ( syn – anti ) isomers are detected by 1 H NMR spectroscopy 21. We also demonstrated that the inclusion of tertiary amino groups as hydrogen bond donors in the vicinity of the squaramido NH groups induces formation of β‐turn analogues in secondary squaramides, allowing the synthesis of oligomeric cyclosquaramides through hydrogen‐bond‐directed macrocyclization 22…”
Section: Introductionmentioning
confidence: 67%
“…Oligosquaramides C2 and C5 were synthesized as reported previously. [13] The stock solutions of oligosquaramides were obtained as follows: 60 mg were dissolved in 70 mL of HCl 3 m. The resultant solution is diluted up to a final volume of 500 mL in DMSO. Total clarity of the solution was achieved typically with soft heating (T < 60 8C) for a few minutes.…”
Section: Methodsmentioning
confidence: 99%
“…Cyclic oligosquaramides have been synthesized successfully by Rotger et al, [13] showing antitumoral activity, as well as inhibition of kinases, with low toxicity.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the diamido-derivatives (also known as squaramides) have been studied in the conttext of molecular recognition, 13 supramolecular assemblies, 14,15 and as improved chiral organocatalysts. These properties have been applied to enhance the biological activity of several drugs and to functionalize organic molecules.…”
Section: Chemosensorsmentioning
confidence: 99%